An analysis of the transport infrastructure of Kazakhstan in the field of tourism (Journal of Economic Research & Business Administration, 2016)
As international experience shows the development of the tourism sectorof the economy is a source of economic development. But the industryis, in turn, requires a set of measures for development. These include transport,infrastructure, trade, health, etc. In turn, from vyssheskazannogo specialattention must be paid to transport infrastructure. The rapid developmentof the economy promotes the growth of large-scale industrializationand modernization of foreign economic relations of production, transportand logistics capabilities. Taking into account the unique geographical positionof our country, as well as the convenience of major transport routesin Eurasia, Kazakhstan has to take the initiative on the creation of a largetransit hub. The country is located in the center of the Eurasian continentwith great transit potential of the large volume of freight traffic, and sootvntstvennoshould be integrated into the international transport system. Inorder to enter into the international economic system began constructionof the road, naming the Great Silk Road of XXI century «Western Europe -Western China».
Keywords: transport infrastructure; transit potential; tourism infrastructure; transport services market.